Золотая роза - Паустовский Константин Георгиевич (Внеклассное чтение, 2008)
Экземпляры: (20100210) / Инвентарный номер: 45623 / Цена: 149.27 / Сис.шифр: 84(2Рос=Рус)6 45623 / Авт.знак: П 21 / ББК: 84(2Рос=Рус)6